2013
DOI: 10.1111/echo.12392
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐Related Changes of the Epicardial Fat Thickness and Leptin in Obstructive Sleep Apnea

Abstract: Leptin and EFT may be a valuable parameter in the evaluation of OSA severity in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
2
15
1
Order By: Relevance
“…Leptin concentrations in women are higher than in men [24]. In a cross-sectional study in severely untreated OSAS patients using single leptin measurements, OSAS severity was related to leptin concentrations among females, but not in males [25]. In our study, leptin concentrations did not differ between males and females at baseline; whereas during the follow-up, increase in leptin concentrations was higher among females compared with males.…”
Section: Discussioncontrasting
confidence: 65%
“…Leptin concentrations in women are higher than in men [24]. In a cross-sectional study in severely untreated OSAS patients using single leptin measurements, OSAS severity was related to leptin concentrations among females, but not in males [25]. In our study, leptin concentrations did not differ between males and females at baseline; whereas during the follow-up, increase in leptin concentrations was higher among females compared with males.…”
Section: Discussioncontrasting
confidence: 65%
“…Iacobellis et al showed bigger size of EFT in males than in females [ 17 ], and our result showed the greater values of EFT in females. Recent study by Akilli et al [ 25 ] showed larger EFT in females than in males. Thus, these findings may indicate different gender susceptibilities related to obesity and the regional differences in fat distribution, especially EFT distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies demonstrated a possible association between EAT thickness and OSAHS severity in obese patients [18] and in OSAHS patients with and without metabolic syndrome [19]. Another study was found thicker EAT only in women with severe OSAHS [20].…”
Section: Introductionmentioning
confidence: 92%